1998
DOI: 10.1017/s0022215100142859
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular haemangioma of head and neck region

Abstract: Intramuscular haemangiomas are rare benign haemangiomas occurring within the skeletal muscle. These are uncommon tumours in the head and neck region and occur most frequently on the trunk and extremities. Fewer than 80 cases of intra-muscular haemangioma in the head and neck region have been reported in the literature.A case of intramuscular haemangioma of the sternocleidomastoid muscle is presented. The review of occurrence and natural history of such tumours is described and clinical and radiological present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 7 publications
(12 reference statements)
1
33
0
1
Order By: Relevance
“…8 Chaudhary et al reported a slight male preponderance. 9 In the five previously reported cases (reviewed here) and our case there were a total of two male and four female patients.…”
Section: Discussionmentioning
confidence: 71%
“…8 Chaudhary et al reported a slight male preponderance. 9 In the five previously reported cases (reviewed here) and our case there were a total of two male and four female patients.…”
Section: Discussionmentioning
confidence: 71%
“…Based on predominant vascular pattern they are classified into Capillary, Cavernous and Mixed. Most reports of Intramuscular Haemangioma stress on its atypical clinical presentation [5]. Histopathologically the tumour contains various amount of fibro fatty tissue, smooth muscle, thrombus and bone beside blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Intra muscular hemangiomas-are rare tumors constituting less than 1% of all hemangiomas [5,6]. While there is history of trauma in a sizeable population of patients, it is generally considered a congenital condition [7]. The tumor may be detected in patients aged anywhere between two months to 66 years, however, 80-90% present in patients aged less than 30 years [4].…”
Section: Discussionmentioning
confidence: 99%
“…En-bloc resection of the tumor with the muscle involved is now the treatment of choice, since sclerotherapy and embolotherapy have proven ineffective [7,8]. We chose to excise the entire fl exor digitorum superfi cialis since it had been extensively involved by the hemangioma.…”
Section: Discussionmentioning
confidence: 99%